2022
DOI: 10.3389/fnagi.2022.770136
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Alzheimer’s Disease Molecular Subtypes Based on Parallel Large-Scale Sequencing

Abstract: The incidence of Alzheimer’s disease (AD) is constantly increasing as the older population grows, and no effective treatment is currently available. In this study, we focused on the identification of AD molecular subtypes to facilitate the development of effective drugs. AD sequencing data collected from the Gene Expression Omnibus (GEO) database were subjected to cluster sample analysis. Each sample module was then identified as a specific AD molecular subtype, and the biological processes and pathways were v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Previously, studies have identified molecular signatures of blood cell origin and potential therapeutic targets through a comprehensive analysis of AD-related datasets [44]. Some studies have also analyzed brain tissue samples from AD patients by bioinformatics to look for biomarkers of AD [45][46][47]. Another study was used a web-based approach to identify biomarkers and therapeutic agents for AD [48].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, studies have identified molecular signatures of blood cell origin and potential therapeutic targets through a comprehensive analysis of AD-related datasets [44]. Some studies have also analyzed brain tissue samples from AD patients by bioinformatics to look for biomarkers of AD [45][46][47]. Another study was used a web-based approach to identify biomarkers and therapeutic agents for AD [48].…”
Section: Discussionmentioning
confidence: 99%
“…The protein RBM8A may regulate many genes related to AD pathophysiology ( Zou D. et al, 2019 ). Furthermore, we identified hub genes associated with molecular subtypes as potential biomarkers for AD, as well as candidate therapeutic targets ( Ma et al, 2022 ). Identifying biomarkers for AD and VD may help individualize treatment for patients as a function of their precise symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…CXCR4, EGFR, MAP4K4, IGF1R ( 18 ), and RBM8A ( 19 ) may serve as biomarkers for AD diagnosis. A study identified significant marker genes, which could be related to a potential AD molecular type ( 20 ). Studies have shown that REPS1 serves as a potential biomarker for AD and Vascular dementia that were both associated with Ras signaling ( 21 ).…”
Section: Introductionmentioning
confidence: 99%